The effect of two different rest period lengths on the number of repetitions peformed during resistance training - Miranda, H.; Fleck, S. J.; Simao, R.; Barreto, A. C.; Dantas, E. H. M.; Novaes, J. (The Journal of Strength and Conditioning Research, 2007)
The purpose of this study was to compare the effects of 2 different rest period lengths during a resistance training session with the number of repetitions completed per set of each exercise, the volume completed over 3 sets of each exercise, and the total volume during a training session. Fourteen experienced, weight- trained men volunteered to participate in the study. All subjects completed 2 experimental training sessions. Both sessions consisted of 3 sets of 8 repetitions with an 8 repetition maximum resistance of 6 upper body exercises performed in a set manner (wide grip lat pull-down, close grip pull-down, machine seated row, barbell row lying on a bench, dumbbell seated arm curl, and machine seated arm curl). The 2 experimental sessions differed only in the length of the rest period between sets and exercises: 1 session with a 1-minute and the other with a 3-minute rest period. For all exercises, results demonstrate a significantly lower total number of repetitions for all 3 sets of an exercise when 1-minute rest periods were used (p <= 0.05). The 3- and 1-minute protocols both resulted in a significant decrease from set 1 to set 3 in 4 of the 6 exercises (p <= 0.05), whereas the 1-minute protocol also demonstrated a significant decrease from set 1 to set 2 in 2 of the 6 exercises (p <= 0.05). The results indicate that, during a resistance training session composed of all upper body exercises, 1-minute rest periods result in a decrease in the total number of repetitions performed compared with 3-minute rest periods between sets and exercises.